Improving the Flexibility of Students Through Stick-Based Calisthenics - Siti Aisyah Aisyah; Mita Erliana; Norma Anggara; M. Mulhim (Jurnal Master Penjas & Olahraga, 2026)
This study aims to analyze the improvement in flexibility among students at SMP Negeri 3 Gambut after participating in flexibility training using sticks. The study employed a quantitative approach using an experimental method and a one-group pretest-posttest design. The study population consisted of all 226 students at SMP Negeri 3 Gambut. The sample comprised 25 eighth-grade students selected through purposive sampling. The data collection instrument used the V-Sit and Reach Test to measure flexibility before and after the intervention. The data were analysed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test. The results of the study showed that the mean   score of 16.84 cm increased to 30.28 cm in the posttest, with a significance value of 0.000 < 0.05. These results indicate that body-shaping exercises using a stick had a significant effect on improving the flexibility of the pupils.